Preterm infant outcomes in relation to the gestational age of onset and duration of prelabour rupture of membranes: a retrospective cohort study. Issue 1 (29th December 2017) - Pharande, Pramod; Abdel-Latif, Mohamed E; Bajuk, Barbara; Lui, Kei; Bolisetty, Srinivas
Abstract : Objective: To determine the hospital outcomes of liveborn infants at 23–31 weeks following prelabour preterm rupture of membranes (PPROM). Method: A regional retrospective cohort study of 4454 infants of 23–31 weeks' gestation admitted to a tertiary neonatal network between 2007 and 2011. Primary outcome was the composite chronic lung disease (CLD) or mortality at discharge. Results: 225 (5%) neonates had a history of PPROM occurring prior to 24 +0 weeks (Early-PPROM), 829 (19%) had a history of PPROM at or after 24 +0 weeks' gestation (Late-PPROM) and 3400 (76%) had no history of PPROM (No-PPROM). In comparison to No-PPROM, Early-PPROM group had higher CLD/mortality in infants born at 23–27 weeks (OR 1.95; 95% CI 1.34 to 2.85) and 28–31 weeks (OR 4.98; 95% CI 2.99 to 8.28). Within Early-PPROM group, the latency of PPROM >14 days had lower CLD/mortality in comparison to latency ≤14 days (57.6% vs 77%, OR 0.40; 95% CI 0.21 to 0.76). Late-PPROM group had significantly lower CLD/mortality in comparison to No-PPROM group at 23–27 weeks (OR 0.50; 95% CI 0.37 to 0.69) and 28–31 weeks (OR 0.50; 95% CI 0.36 to 0.71). Within Late-PPROM group, latency >14 days was associated with an increased CLD/mortality in 28–31 weeks (14.1% vs 5.4%, OR 2.88; 95% CI 1.31 to 6.38). Conclusions: Early-PPROM prior to 24 weeks' gestation had high incidence of CLD/mortality even after correcting for gestational age. Late-PPROM at or after 24 weeks had lower CLD/mortality compared with No-PPROM. Latency >14 days in Late-PPROM group at 28–31 week group increased the odds of CLD/mortality.